2003
DOI: 10.1248/bpb.26.120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Storage Conditions and Alterations of Antioxidant Contents on Chromatic Aberration of Hydroquinone Ointment.

Abstract: Ointments of the skin depigmentation agent hydroquinone (HQ) have been prepared by extemporaneous nonsterile compounding in Japan by imitating skin lightening creams commercially available in the U.S.A. and European Union. [1][2][3][4][5][6][7][8] In our hospital, HQ ointments consisting of 5 or 10% HQ, 1.6% L(ϩ)-ascorbic acid (AsA), 0.5% Na 2 SO 3 , 10% (v/w) glycerin and hydrophilic ointment have been prepared (Table 1). 9) However, various problems have been observed during usage for about 4 years including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Of note, topical preparations of hydroquinone are extremely unstable and rapidly discolor in appearance and increase the skin irritation if the hydroquinone-contained formula is exposed to UV irradiation [19]. In this study, we determined the cell viabilities and intracellular ROS levels in monophenol-treated melanocytes in the presence or absence of 3 J/cm 2 UVA exposure, emphasizing whether it is safe to use such skin-lightening ingredients daily in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, topical preparations of hydroquinone are extremely unstable and rapidly discolor in appearance and increase the skin irritation if the hydroquinone-contained formula is exposed to UV irradiation [19]. In this study, we determined the cell viabilities and intracellular ROS levels in monophenol-treated melanocytes in the presence or absence of 3 J/cm 2 UVA exposure, emphasizing whether it is safe to use such skin-lightening ingredients daily in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroquinones and their derivatives are widely used to treat hyperpigmentation in many countries but, they are unstable and easily oxidized. 34) Therefore a new tyrosinase inhibitor is needed. SG-8 showed so much cytotoxicity that it could not be considered as a melanin regulator.…”
Section: Fig 5 Sg-8 Has An Uncompetitive Inhibitory Effect On Mushrmentioning
confidence: 99%
“…9,10) p-BQ was detected at a level of 0.1-0.5% of HQ in antioxidant-free HQ ointments, but this decreased to 0-0.05% on addition of AsA and Na 2 SO 3 . 9,10) Here, it was also demonstrated that the cytotoxicity of HQ was not altered by antioxidants, AsA and Na 2 SO 3 . Consequently, it was suggested that p-BQ was not extensively cytotoxic in FR cells.…”
Section: Resultsmentioning
confidence: 73%
“…9,10) However, various problems have been observed during usage including chromatic aberration of the ointments, a relatively large variability of efficacy, and undesirable topical side effects, e.g., irritation, although they were mild. The pharmaceutical and clinical properties of HQ ointments prepared in our hospital have been evaluated, 9,10) and the following observations were made: 1) HQ ointments were highly effective in the treatment of various types of skin pigmentations; 2) Chromatic aberration occurred during 3 months of storage at room temperature, and was accelerated by exposure to high temperature, air and light; 3) Chromatic aberration was independent of the prescribed HQ content, and was not explained by alterations in the content of HQ or p-benzoquinone (p-BQ), which was formed from HQ; 4) Removal of both antioxidants resulted in the suppression of chromatic aberration; 5) Removal of Na 2 SO 3 only was further effective in suppressing chromatic aberration, and the protective effect of AsA was mainly due to its acidifying effect; 6) Chromatic aberration was due to a newly developed water-soluble material and insoluble non-covalent complex both formed by HQ and p-BQ.In this paper, to evaluate whether the topical side effects including irritation after application of the HQ ointments are due to HQ, AsA and Na 2 SO 3 , their cytotoxicity was assessed in vitro using rat skin fibroblasts as the concentration with 50% survival after 24 h exposure. 11,12) Results were compared with the intradermal concentrations after application of the HQ ointments, which were estimated by an in vitro rat skin permeation study with rat full-thickness abdominal skin and Franz-type diffusion cells.…”
mentioning
confidence: 99%